PRINSIP PEMERINTAHAN DALAM ISLAM MENURUT MUHAMMAD ASAD - Tasnim Abdul Rahman; Ahmad Nabil Amir, (Journal of Human Development and Communication (JoHDeC), 2025)
This paper discusses Muhammad Asad’s work on the principle of Islamic governance and its basic constitution and foundational structure. In this regard, he formulated the constitutional ideas of Islamic state whose constitution contains the provision of Islamic law that practiced and implement the norms stated in the Qur’an and hadith. This idea was partly enshrined in the Pakistan constitutional law whose political establishment was formed in 1947. It essentially discussed Muhammad Asad’s political ideas and its underlying philosophy as espoused in his works, such as The principles of state and government in Islam, This law of ours and other essays, Islamic constitution making, journal Arafat, The message of the Qur’an, Sahih al-Bukhari the early years of Islam and, etcetera. The study is based on qualitative methods in the form of library research. The data were analysed using descriptive, analytical and comparative methods. The finding shows that Muhammad Asad had formulated comprehensive theoretical framework of legal aspect of Islamic governance based on the fundamental principle and doctrine of the shariah, derived from the teaching of the Qur’an and the sunnah, while advocating democratic ideals and system based on conventional practice and requirement of modern context of nation state. Makalah ini membincangkan karya seminal Muhammad Asad tentang prinsip pemerintahan Islam dan struktur dasar dan asas-asas konstitusionalnya. Dalam hal ini, beliau telah merumuskan idea-idea keperlembagaan tentang negara Islam yang konstitusinya mengandungi peruntukan-peruntukan syariah yang menerapkan norma-norma yang tercatat dalam al-Qur’an dan hadith. Idea ini sebahagiannya dimasyhurkan dalam undang-undang dasar Pakistan pada bahagian pengantarnya yang pentadbiran politiknya dibentuk pada 1947. Kertas ini pada asasnya membahaskan idea-idea politik Muhammad Asad dan landas falsafahnya yang diungkapkan dalam karya-karyanya, seperti The principles of state and government in Islam, This law of ours and other essays, Islamic constitution making, journal Arafat, The message of the Qur’an, Sahih al-Bukhari the early years of Islam dan lain-lain. Kajian ini dirangka berasaskan metode kualitatif dari jenis tinjauan pustaka dan dokumenter. Data dianalisis secara deskriptif, analitik, dan komparatif. Temuan kajian menunjukkan bahawa Muhammad Asad telah merumuskan kerangka teoretikal yang komprehensif tentang aspek-aspek perundangan dan hukum yang terpakai dalam negara Islam berasaskan prinsip dan doktrin shariah yang fundamental, yang diambil dari keterangan al-Qur’an dan sunnah, sementara dalam masa yang sama turut mengadvokasikan ideal-ideal demokratik dan pendirian sistem multilateral berasaskan praktik konvensional dalam konteks negara bangsa yang moden.